Histodynamics of Natural Killer Cells from a Healthy Donor Exposed to Exosomes from the Blood of Hepatocellular Carcinoma Patients - Asrinda, Indria; Antarianto, Radiana Dhewayani; Jusuf, Ahmad Aulia; Ahani, Ardhi Rahman; Jasirwan, Chyntia Olivia Maurine; Ritchie, Ni Ken; Nur Aditya, Robby; Irawan, Cosphiadi (UI Scholars Hub, 2024)
Background: Hepatocellular carcinoma (HCC) is the leading form of liver cancer and the second leading cause of cancer-related deaths globally. Exosomes in the HCC microenvironment can induce significant changes in natural killer (NK) cells during endocytosis. The present study aimed to distinguish exosomes in the blood of HCC patients, analyze changes in NK cell phenotype, and evaluate peroxidase and toluidine blue staining as alternative methods for observing the changes. Methods: NK cells were collected from healthy donors, and exosomes were extracted from the blood of HCC patients. The exosomes were characterized in accordance with MISEV 2018 guidelines, and NK cells were incubated with HCC-derived exosomes. NK cell phenotype changes were assessed using immunofluorescence, toluidine blue staining, and peroxidase staining. Results: The identified exosomes measured 34.7 nm, had a charge of −4.33 mV, and were positive for CD81+. Changes in NK cell receptor expression following exposure to HCC exosomes were not significant (p > 0.05). Immunofluorescence confirmed exosome endocytosis by NK cells, toluidine blue staining revealed negative metachromasia and peroxidase staining indicated morphological NK cell changes. Conclusions: This study demonstrates that peroxidase and toluidine blue staining are effective for observing exosome endocytosis in NK cells, enhancing our understanding of HCC exosome-NK cell interactions and beneficial in developing future therapeutic strategies targeting the HCC microenvironment.